A new species of Diplolepis Geoffroy (Hymenoptera: Cynipidae: Diplolepidini) from northeastern China - Zhu, Qifan; Looney, Chris; Chen, Tianlin; Cuesta-Porta, Víctor; Zoltán, László; Wang, Yiping; Pujade-Villar, Juli (Zootaxa, 2021)
A new species, Diplolepis valtonyci Zhu, Wang & Pujade-Villar sp. nova, is described from Rosa rugosa Thunb. (1784) and R. davurica Pall. (1788) from China using an integrative approach based on molecular and morphological data. Diagnosis, distribution, and biology of the new species are given and illustrated. The phylogenetic relationship between D. valtonyci sp. nova and other Diplolepis species are assessed based on COI and Cytb genes. A key to the Chinese species of Diplolepis is provided.